2004
DOI: 10.1017/s1743921304005575
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Dynamics of Solar Filaments - challenges in observing and modeling

Abstract: Abstract. Fundamental information about the nature of solar filaments and governing physical processes are retained in their small-scale structure and dynamics. The paper reviews some recent high resolution studies of filaments, with emphasize on potential impact on current understanding of their physical nature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 16 publications
(22 reference statements)
1
16
0
Order By: Relevance
“…Chiuderi Drago et al 1983;Loukitcheva et al 2004Loukitcheva et al , 2006 are usually based on the VAL (Vernazza et al 1981), FAL (Fontenla et al 1993), and CS (Carlsson & Stein 1992, 1995, 2002) models. Modeling of filaments radio emission (or absorption) is not straightforward, since the results are strongly frequency dependent, especially in the mm and sub-mm wavelength range (Chiuderi Drago 1990;Chiuderi & Chiuderi Drago 1991;Chuideri Drago et al 1992;Engvold 1994;Tandberg-Hanssen 1995). Moreover, many subtle effects should be taken into account, e.g., the influence of the prominence-corona transition region, or the visibility of filament channels and coronal condensations.…”
Section: Introductionmentioning
confidence: 99%
“…Chiuderi Drago et al 1983;Loukitcheva et al 2004Loukitcheva et al , 2006 are usually based on the VAL (Vernazza et al 1981), FAL (Fontenla et al 1993), and CS (Carlsson & Stein 1992, 1995, 2002) models. Modeling of filaments radio emission (or absorption) is not straightforward, since the results are strongly frequency dependent, especially in the mm and sub-mm wavelength range (Chiuderi Drago 1990;Chiuderi & Chiuderi Drago 1991;Chuideri Drago et al 1992;Engvold 1994;Tandberg-Hanssen 1995). Moreover, many subtle effects should be taken into account, e.g., the influence of the prominence-corona transition region, or the visibility of filament channels and coronal condensations.…”
Section: Introductionmentioning
confidence: 99%
“…High-resolution observations have shown that the filament spine is composed of a collection of separate threads (Engvold, 2004;Lin et al, 2005). These threads are believed to be the building blocks of filaments.…”
Section: Introductionmentioning
confidence: 99%
“…They have been interpreted in terms of magnetohydrodynamic (MHD) eigenmodes of the magnetic structure and/or propagating MHD waves. The reader is referred to some recent reviews for more information about the observational and theoretical backgrounds (Oliver & Ballester 2002;Engvold 2004;Ballester 2006;Banerjee et al 2007;Engvold 2008).…”
Section: Introductionmentioning
confidence: 99%